Telling our stories: heroin-assisted treatment and SNAP activism in the Downtown Eastside of Vancouver - Susan Boyd; Dave Murray; SNAP; Donald MacPherson (Harm Reduction Journal, 2017)
Abstract Background This article highlights the experiences of a peer-run group, SALOME/NAOMI Association of Patients (SNAP), that meets weekly in the Downtown Eastside of Vancouver, British Columbia, Canada. SNAP is a unique independent peer- run drug user group that formed in 2011 following Canada’s first heroin-assisted treatment trial (HAT), North America Opiate Medication Initiative (NAOMI). SNAP’s members are now made up of former research participants who participated in two heroin-assisted trials in Vancouver. This article highlights SNAP members’ experiences as research subjects in Canada’s second clinical trial conducted in Vancouver, Study to Assess Longer-term Opioid Medication Effectiveness (SALOME), that began recruitment of research participants in 2011. Methods This paper draws on one brainstorming session, three focus groups, and field notes, with the SALOME/NAOMI Association of Patients (SNAP) in late 2013 about their experiences as research subjects in Canada’s second clinical trial, SALOME in the DTES of Vancouver, and fieldwork from a 6-year period (March 2011 to February 2017) with SNAP members. SNAP’s research draws on research principles developed by drug user groups and critical methodological frameworks on community-based research for social justice. Results The results illuminate how participating in the SALOME clinical trial impacted the lives of SNAP members. In addition, the findings reveal how SNAP member’s advocacy for HAT impacts the group in positive ways. Seven major themes emerged from the analysis of the brainstorming and focus groups: life prior to SALOME, the clinic setting and routine, stability, 6-month transition, support, exiting the trial and ethics, and collective action, including their participation in a constitutional challenge in the Supreme Court of BC to continue receiving HAT once the SALOME trial ended. Conclusions HAT benefits SNAP members. They argue that permanent HAT programs should be established in Canada because they are an effective harm reduction initiative, one that also reduces opioid overdose deaths.